5.8 GHz circularly polarized rectangular microstrip antenna arrays simulation for point-to-point application - Mohd Aminudin, Jamlos; Nurasma Husna, Mohd Sabri; Mohd Faizal, Jamlos; Wan Azani, Mustafa; Syed Zulkarnain, Syed Idrus; Mohamad Nur Khairul Hafizi, Rohani; Khairul Najmy, Abdul Rani; Mohd Al Hafiz, Mohd Nawi (Penerbit Akademia Baru, 2022)
In this paper, the design and simulation of rectangular microstrip antenna arrays for improving antenna gain is performed for point-to-point application. The circular polarization is proposed to restrict the limitation of linear polarization which is less reliable in base station antenna. The circular polarization antenna is made to allow the receiver constantly to receive the power at any wave angle and make the transmission between two antennas are more constant. The proposed design is composed of four elements microstrip antenna with an array configuration operating at 5.8 GHz. Each element is constructed from four truncated arrays radiating elements and an inclined slot on each patch which capable to achieve circular polarized capability. The design of the 2x1 and 2x2 of rectangular microstrip array antenna was implemented from the design of single rectangular patch antenna as the basic building element. The designed 2x1 and 2x2 array were fed by microstrip transmission line which applied a technique of quarter wave impedance matching. The antenna design was etched on Rogers RT 5880 substrate with 2.1 and 1.53 mm of dielectric constant and thickness respectively. All the designed structure were simulated in CST software. The main results of the designed antennas were compared in terms of gain, axial ratio and return loss. Based on the return loss simulation results, the designed antennas resonated exactly at the desired resonant frequency of 5.8 GHz which indicates good antenna designs. Compared to the single patch antenna having an antenna gain of 8.26 dB, the 2x1 and 2x2 arrays achieved a gain of 10.24 dB and 13.29 dB respectively. The results show that the designed rectangular microstrip antenna arrays have an improved gain performance over the single patch antenna.